Sexual dimorphism of miRNA expression: a new perspective in understanding the sex bias of autoimmune diseases - Dai R; Ahmed SA (Dove Medical Press, 2014)
Rujuan Dai, S Ansar Ahmed Department of Biomedical Sciences and Pathobiology, Virginia-Maryland Regional College of Veterinary Medicine, Virginia Tech, Blacksburg, VA, USA Abstract: Autoimmune diseases encompass a diverse group of diseases which emanate from a dysregulated immune system that launches a damaging attack on its own tissues. Autoimmune attacks on self tissues can occur in any organ or body system. A notable feature of autoimmune disease is that a majority of these disorders occur predominantly in females. The precise basis of sex bias in autoimmune diseases is complex and potentially involves sex chromosomes, sex hormones, and sex-specific gene regulation in response to internal and external stimuli. Epigenetic regulation of genes, especially by microRNAs (miRNAs), is now attracting significant attention. miRNAs are small, non-protein-coding RNAs that are predicted to regulate a majority of human genes, including those involved in immune regulation. Therefore, it is not surprising that dysregulated miRNAs are evident in many diseases, including autoimmune diseases. Because there are marked sex differences in the incidence of autoimmune diseases, this review focuses on the role of sex factors on miRNA expression in the context of autoimmune diseases, an aspect not addressed thus far. Here, we initially review miRNA biogenesis and miRNA regulation of immunity and autoimmunity. We then summarize the recent findings of sexual dimorphism of miRNA expression in diverse tissues, which imply a critical role of miRNA in sex differentiation and in sex-specific regulation of tissue development and/or function. We also discuss the important contribution of the X chromosome and sex hormones to the sexual dimorphism of miRNA expression. Understanding sexually dimorphic miRNA expression in sex-biased autoimmune diseases not only offers us new insight into the mechanism of sex bias of the disease but will also aid us in developing new sex-based therapeutic strategies for the efficient treatment of these diseases with a sex bias. Keywords: sex differences, microRNA, immune regulation, autoimmune diseases, X chromosome, sex hormones